EFFECTS OF INSITU MOISTURE CONTENT ON PAVEMENT OF LOW VOLUME SEALED ROADS - Odero, Peter Otieno; Gariy, Z.A (International Journal of Technology and Systems, 2020)
Purpose: This paper seeks to assess the effects of the in-situ moisture on pavement and subgrade strength. This is done through determination of in-situ CBR and DCP correlations at varying moisture regimes. When tested using the DCP device to assess the in-situ conditions the information can be used to identify uniform section, the layer strength diagrams and this can be used to determine layer depth, quality and in-situ moisture. Methodology: Two roads with varying climatic conditions, soil types but almost similar traffic levels were identified for this research. The Road sections were D470 Kyeni - Karurumo and E628 Wamumu Karaba. The tests on the roads pavement were carried out in three stages: Before construction, During construction and After allowing traffic to flow. Samples were taken from the road section before any improvement for testing. The test included; Classification test including grading, atterberg limits and linear shrinkage, Compaction test including MDD and OMC, Strength test including CBR soaked, OMC and 0.75 OMC, Pavement layer properties including IDD and MC, Field confirmation of road side drainage Findings: The study found out that that the more the in-situ moisture is reduced from the pavement structure the stronger the pavement. Knowledge of the inter relationship between the moisture, density and strength of the material used in the construction of LVSRs provides critical insight into how to use such materials to ensure good performance in the prevailing road environment. Unique Contribution to Theory, Practice and Policy: The unique contribution of the research is acceleration of the improvement of road construction through correlation of DCP-CBR and allowing use of locally available materials.